Integrating Cybersecurity and Digital Marketing Intelligence to Enhance Global Competitiveness in U.S. Manufacturing - Shahi, Durga; Sizan, Arif Ahmed; Ridoy, Jakir Hossain; Utsho, Mashuk Rahman; Rashid, Md Mohaimin; Alam, Md Shayakh; Noor, Syeda Kamari; ., Raiyan (Journal of Posthumanism, 2025)
Background: The United States has long been a dominant player in the global export market, with the manufacturing sector contributing significantly to the economy. In the face of growing competition and changing global dynamics, U.S. manufacturers are increasingly turning to digital marketing strategies to maintain and expand their international market share. Digital marketing has become a vital tool for enhancing visibility, engagement, and ultimately driving export growth. Objectives: This study aims to explore the impact of four key digital marketing strategies—Search Engine Optimization (SEO), Search Engine Marketing (SEM), Social Media Marketing (SMM), and Online Direct-to-Customer Sales (ODTC)—on the export performance of U.S. manufacturing firms. It seeks to identify the most effective strategies and evaluate how integrating these tactics can reduce barriers to export growth and enhance international market penetration. Methodology: The research utilizes an exploratory quantitative design with a structured survey distributed to a large sample of U.S. manufacturers engaged in exporting. Data was analyzed using statistical software (SPSS) to perform correlation analysis, multiple regression, and ANOVA to assess the relationship between digital marketing strategies and export performance. Results: The findings suggest that while individual strategies such as SEO show limited impact when used alone, integrated approaches, particularly involving SMM and ODTC, significantly enhance export performance. SEM also showed improvements when combined with other strategies, further supporting the need for an integrated marketing approach. Conclusion: Digital marketing, when applied strategically and integrated across various channels, holds substantial potential for boosting the export performance of U.S. manufacturing firms. The study emphasizes the importance of combining SEO, SEM, SMM, and ODTC to drive market growth and overcome international export barriers. Future research should continue to explore the long-term impacts of these strategies on global market expansion.